Comparative Effectiveness of Powerpoint Over OHP as an Effective Teaching Learning Tool at R.D. Gardi Medical College Ujjain (M.P) (International Journal of Physiology, 2022)
Background: Since years, a number of initiatives were taken to improve the teaching methodology in Medicaleducation.Objective: The present study was undertaken to emphasize the importance of LCD-based teaching over OHP andto increase teachers’ acceptability to LCD.Materials and methods: This study was carried out with 100- 125 students. The study incorporated 50 minutesteaching sessions in the department of physiology with the use of two different teaching tools. Students weredivided into two groups. One topic was selected and Roll numbers 1 to 75 were taught by Powerpoint by LCDs& students from roll number 76 to 150 by Transparencies, in the second week they were assessed by written test.Results: Significant difference in marks obtained by the students taught on PPT as compared to OHP(P>.001)it was observed that students who scored less after OHP exposure showed improvement after PPT exposure.(Table 1& 2) 80% of students prefer PPT over OHP and understanding of the subject was more with PPT. Studentsfound OHP good for the text material and insufficient for the applied and diagram part while preferred PPT for3-D view of diagrams, concepts and applied.Conclusion: In Department of Physiology at our Institute most preferred TL method was found to be by PPT thenOHP. As results also indicated improved performance by the students, In view of that Teachers also agreed to theresponses by the students, and showed acceptability for PPT.Keywords: Teaching learning method; students; Medical education.